Benefit analysis of the implementation of Environmental Management System (EMS) ISO 14001:2015 in a tyres industry - Hidayati, Ruti Nurul; Sodikin, Sodikin; Nurhasanah, Nurhasanah (Universitas Pakuan, 2023)
Environmental management has an important role in PT. Elang Perdana Tyres Industry (PT. EPTI). The company has been implementing a standard of ISO 14001:2015 to implement its environmental management. Environmental Management System (EMS) ISO 14001:2015 implemented consistently and effectively, provides several benefits that can enhance environmental performance in the company. The objectives of this research are 1) to identify the benefits of the implementation of EMS ISO 14001:2015, and 2) to analyze the relationship between the benefits of the implementation of EMS ISO 14001:2015 and the environmental performance of EMS. Primary data was collected from field observations, interviews with respondents, and questionnaire surveys. Secondary data was obtained from company profile, and organizational structure, as well as documents of ISO 14001:2015. This research explained that the benefits of the implementation of the Environmental Management System (EMS) ISO 14001:2015 are enhancing company reputation, enhancing customer satisfaction, enhancing employee motivation, and reducing production costs. The main benefit for the company, based on the questionnaire result of 100 respondents determined from the Slovin formula, is enhancing the company's reputation (93 respondents). Besides, this research also explains that the implementation of EMS ISO 14001:2015 has a strong relationship with the environmental performance of EMS ISO 14001:2015 (coefficient of regression 0,717). Therefore, the benefits of the implementation of the Environmental Management System (EMS) ISO 14001:2015 are enhancing company reputation, enhancing customer satisfaction, enhancing employee motivation, and decreasing production costs have a strong relationship with environmental performance EMS ISO 14001:2015 in PT. EPTI. Benefit analysis of the implementation of EMS ISO 14001:2015 is needed to inform the company about the importance of benefits that can be obtained for improving the implementation of EMS ISO 14001:2015. The benefits obtained by the company will attract and motivate the company to improve the performance of EMS ISO 14001:2015. Even these benefits will further motivate continuous improvement that has an impact on effective environmental management in reducing negative environmental impacts and supporting sustainable development as a whole. Pengelolaan lingkungan mempunyai peranan penting di PT. Elang Perdana Tyres Industry (PT. EPTI). Perusahaan telah menerapkan standar ISO 14001:2015 untuk menerapkan pengelolaan lingkungannya. Sistem Manajemen Lingkungan (EMS) ISO 14001:2015 yang diterapkan secara konsisten dan efektif, memberikan beberapa manfaat yang dapat meningkatkan kinerja lingkungan di perusahaan. Tujuan penelitian ini adalah 1) mengidentifikasi manfaat penerapan EMS ISO 14001:2015, dan 2) menganalisis hubungan manfaat penerapan EMS ISO 14001:2015 dengan kinerja lingkungan EMS. Data primer dikumpulkan dari observasi lapangan, wawancara terhadap responden, dan survei kuesioner. Data sekunder diperoleh dari profil perusahaan, dan struktur organisasi, serta dokumen ISO 14001:2015. Penelitian ini menjelaskan bahwa manfaat penerapan Sistem Manajemen Lingkungan (EMS) ISO 14001:2015 adalah meningkatkan reputasi perusahaan, meningkatkan kepuasan pelanggan, meningkatkan motivasi karyawan, dan mengurangi biaya produksi. Manfaat utama bagi perusahaan berdasarkan hasil kuesioner terhadap 100 responden yang ditentukan dari rumus Slovin adalah meningkatkan reputasi perusahaan (93 responden). Selain itu penelitian ini juga menjelaskan bahwa penerapan EMS ISO 14001:2015 mempunyai hubungan yang kuat dengan kinerja lingkungan EMS ISO 14001:2015 (koefisien regresi 0,717). Oleh karena itu, manfaat penerapan Sistem Manajemen Lingkungan (EMS) ISO 14001:2015 adalah meningkatkan reputasi perusahaan, meningkatkan kepuasan pelanggan, meningkatkan motivasi karyawan, dan menurunkan biaya produksi mempunyai hubungan yang kuat dengan kinerja lingkungan EMS ISO 14001:2015 di PT. EPTI. Analisis manfaat penerapan EMS ISO 14001:2015 diperlukan untuk memberikan informasi kepada perusahaan mengenai pentingnya manfaat yang dapat diperoleh untuk perbaikan penerapan EMS ISO 14001:2015. Manfaat yang diperoleh perusahaan akan menarik dan memotivasi perusahaan untuk meningkatkan kinerja EMS ISO 14001:2015. Bahkan manfaat-manfaat tersebut akan semakin memotivasi perbaikan berkelanjutan yang berdampak pada pengelolaan lingkungan hidup yang efektif dalam mengurangi dampak negatif terhadap lingkungan dan mendukung pembangunan berkelanjutan secara keseluruhan.